Bad Surprises of Servitisation: Environmental consequences of Value Creation - Sukumar, Hariharan T; Ganesh, L.S.; Sharma, Piyush; Vijayalakshmi, V.; Potdar, Vidyasagar (2019)
Servitisation is a relatively new concept in the literature of marketing and strategy, in which products are services are bundled together as a system. Servitisation is said to improve the firm’s value, customer retention, etc. The output of servitisation is Product-Service Systems, which are touted as environment-friendly business models. However, not all servitisation models are environmentally benign. This article, using qualitative system dynamics methodology and specifically causal loop digrams, argues that certain PSS models such as product leasing, product renting, pay-per-use/services increase the affordability of the use of products thereby increasing the overall consumption There are also environmental advantages of servitisation with respect to the disposal of used products and obsolescence practices that can be leveraged. This study has both theoretical and practical implication; businesses can understand the environmental impact of their PSS business models and can plan mitigatory efforts, policymakers can design appropriate incentives for businesses and consumers based on environmental impacts of PSS busines models.